Monitoring off-resonance signals with SHARPER NMR – the MR-SHARPER experiment. Issue 8 (25th March 2022) - Davy, Matthew; Dickson, Claire L.; Wei, Ran; Uhrín, Dusan; Butts, Craig P.
Abstract : We extend the SHARPER NMR method designed to accommodate challenging reaction conditions to monitor simultaneously multiple resonances such as those of a reactant (2, 6-difluoro-4-methoxyphenylboronic acid) and product (3, 5-difluoroanisole). Abstract : We demonstrate an extension to the SHARPER (Sensitive Homogenous and Refocussed Peaks in Real Time) NMR experiment which allows more than one signal to be monitored simultaneously, while still giving ultra-sharp, homo- and hetero-decoupled NMR signals. This is especially valuable in situations where magnetic field inhomogeneity would normally make NMR a problematic tool, for example when gas evolution is occurring during reaction monitoring. The originally reported SHARPER experiment only works for a single, on-resonance NMR signal, but here we demonstrate the Multiple Resonance SHARPER approach can be developed, which in principle can acquire multiple on-/off-resonance signals simultaneously while retaining the desirable properties of the parent sequence. In practice, the case of two resonances, e.g. those of a reactant and a product, will most of the time be considered for MR-SHARPER, as illustrated here.